Breast size dissatisfaction, but not body dissatisfaction, is associated with breast self-examination frequency and breast change detection in British women. (March 2018) - Swami, Viren; Furnham, Adrian
Highlights: Greater breast size dissatisfaction (BSD) associated with less frequent breast self-examination. Greater BDE associated with lower confidence detecting breast change. Greater BDE associated with greater delay in consulting doctor following breast change. Body dissatisfaction not associated with breast self-examination frequency. Abstract: Studies examining associations between body image and breast self-examination (BSE) have returned mixed findings, but this may be a function of focusing on global body image. Here, we examined the impact of breast size dissatisfaction specifically on BSE and behaviours in relation to breast change detection. A total of 384 British women completed measures of breast size dissatisfaction, body dissatisfaction, BSE frequency, confidence in detecting breast change, and delay in contacting their doctor upon detecting a breast change. Regression analyses indicated that greater breast size dissatisfaction, but not body dissatisfaction, was significantly associated with less frequent BSE and lower confidence in detecting breast change. Both breast size and body dissatisfaction were significantly associated with greater delay in consulting a doctor following breast change, but the former was the stronger predictor. These findings suggest that improving breast size satisfaction may be a useful means of promoting improved breast awareness and self-examination.